Diagnostic Accuracy of Sonosalpingography for Assessing Tubal Patency in Women with Infertility Taking Laparoscopy as the Gold Standard - Maryam Ahmad Qureshi, Owais Bin Qadeer Gill, Zafar Iqbal, Umber Arooj Tahir, Amna Khalid, Amera Tariq, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the diagnostic validity of Sonosalphingography as a tubal patency test in infertile women using laparoscopy as gold standard. Methodology: This study was carried out at the Shifa International Hospital Islamabad, and the duration of this study was from January 2021 to June 2021. We used the WHO method for sample size by taking the prevalence of tuboperitoneal factors as 30%, sensitivity 72.9%, specificity 81.22%, margin of error 12%, and 95% confidence interval. It was a cross-sectional study that lasted for 6 months and assessed a total of 178 patients. Additionally, a non-probability, sequential sampling strategy was utilized to acquire the sample. Results: Our patients aged between 18-45 years, out of which 30% of the participants aged 18 to 25 years, 55% were between 26 and 35 years, and 15% were between 36 and 45 years. Standard deviation was 1.26, with a mean age of 27. The data collected from both the diagnostic tests was analyzed, diagnostic accuracy of Sonosalphingography was calculated as a sensitivity of 81%, specificity of 76%, positive predictive value of 90%, negative predictive value of 60%, and diagnostic accuracy of 79%. Conclusion: According to the results of our study, Sonosalphingography is a very helpful supplemental diagnostic tool for evaluating tubal disease in patients with infertility, though direct laparoscopic assessment is the gold standard. Sonosalphingography and laparoscopy can be used to evaluate patients with secondary infertility. This spares the patient from being exposed to radiations and the discomfort of contrast administration in HSG. Keywords: Diagnostic Accuracy, Sonosalphingography, Tubal Patency, Infertility, Laparoscopy